A Network-Based Method for Mechanistic Investigation and Neuroprotective Effect on Post-treatment of Senkyunolid-H Against Cerebral Ischemic Stroke in Mouse - Zhang, Jie; Jiang, Yunyao; Liu, Nan; Shen, Ting; Jung, Hyo Won; Liu, Jianxun; Yan, Bing Chun (Frontiers in Neurology, 2019)
Senkyunolide-H (SEH), a major bioactive compound extracted from Ligusticum chuanxiong, has been reported to be effective in preventing cerebral ischemic stroke (CIS). In this study, we employed network pharmacology to reveal potential mechanism of SEH against CIS on a system level and confirmed the therapeutic effects of SEH on CIS by models of cerebral ischemia-reperfusion in vivo and in vitro. Through protein-protein interaction networks construction of SEH- and CIS-related targets, a total of 62 key targets were obtained by screening topological indices and analyzed for Gene Ontology and Kyoto Encyclopedia of Genes and Genomes pathway enrichment. Gene Ontology analysis indicated that SEH might have a role in treating CIS via regulating some biological processes including regulation of transcription from RNA polymerase II promoter, epidermal growth factor receptor signaling pathway, phosphatidylinositol-mediated signaling, and some molecular function, such as transcription factor and protein phosphatase binding and nitric oxide synthase regulator activity. Meanwhile, the Kyoto Encyclopedia of Genes and Genomes analysis showed that phosphoinositide 3-kinase (PI3K)/protein kinase B (Akt) signaling pathway was significantly enriched. In addition, our result showed that SEH posttreatment significantly decreased the neurological scores, infarct volume, and neuronal death in the middle cerebral artery occlusion mice. Moreover, the PI3K/Akt/nuclear factor kappa B signaling pathway was activated by intragastric administration of 40 mg/kg SEH, as verified by Western blot. In vitro, treatment of PC12 cells with 100 μM SEH markedly reduced cell death induced by oxygen-glucose deprivation through the activation of PI3K/Akt/nuclear factor kappa B pathway, and the therapeutic effect of SEH was obviously inhibited by 10 μM LY294002. In summary, these results suggested that SEH carries a therapeutic potential in CIS involving multiple targets and pathways, and the most crucial mechanism might be through the activation of PI3K/Akt/nuclear factor kappa B (NF-κB) signaling pathway to inhibit inflammatory factor releases and increase the antiapoptosis capacity. Our study furnishes the future traditional Chinese medicine research with a network pharmacology framework.